Implementasi Program Peningkatan Peranan Wanita Menuju Keluarga Sehat dan Sejahtera (P2WKSS) di Desa Sukadaya Kabupaten Bekasi - Rejbiani, Alifya Gita; Hakim, Lukmanul; Azijah, Dewi Noor (Universitas 17 Agustus 1945 Surabaya, 2021)
Research related to the implementation of the P2WKSS program in Sukadaya Village has not been researched, so it is hoped that by carrying out research related to P2WKSS in order to know the extent to which the P2WKSS Program in Sukadaya Village has been implemented and becomes material for evaluating the Bekasi Regency Government in implementing and implementing the P2WKSS program in Sukadaya Village and for in subsequent villages. This study was analyzed using an analysis knife of the implementation theory. Rondinelli. This research is located in Sukadaya Village. Researchers examined problems regarding the implementation of the P2WKSS program in Sukadaya Village through a qualitative approach with descriptive methods. Sources of data that researchers use in research related to P2WKSS use primary and secondary. Data collection was carried out in 3 ways, namely: interviews, observation and documentation. The data analysis technique is done by reducing, presenting and drawing conclusions. The results of the research analysis explained that the P2WKSS program in Sukadaya Village has been implemented quite well, as many assisted residents have benefited from this program such as the Sukadaya Village environment so that it is more neatly organized and the assisted residents can increase their knowledge and skills, but its implementation is not optimal because the lack of budget in the aspect of sustainability causes the assisted residents to find it difficult to obtain capital to develop their skills so that many empowerments do not work.